Pharmacotherapy and other aspects of senior medical students' knowledge in community-acquired pneumonia: the final results of the KNOCAP II project - Roman A. Bontsevich; Anna A. Gavrilova; Anna V. Adonina; Yana R. Vovk; Natalya Y. Goncharova; Galina A. Batisheva; Olga V. Cherenkova; Olena V. Myronenko; Elena V. Luchinina; Valeriya O. Barysheva; Galina G. Ketova; Elena N. Bochanova; et al. (Belgorod National Research University, 2020)
Introduction: Community-acquired pneumonia (CAP) remains an extensive medical and social problem. It is the most common human disease and one of the leading causes of death from infectious diseases. Increasing the level of senior medical students' knowledge of the diagnosis, treatment and prevention of CAP will improve the level of medical care to the population. The aim of the study: to determine the level of senior medical students' basic knowledge of CAP prevention, diagnosis and treatment with the help of a pharmacoepidemiological study. Materials and methods: The multicenter study "KNOCAP" (the full name of the project "The Assessment of Physicians' and Students' Knowledge of Community-acquired Pneumonia Basics") presents the results of an anonymous prospective survey aimed at assessing the knowledge and preferences of senior medical students in terms of the CAP pharmacotherapy. In the second stage of the project (2017-2019). The results from 394 senior students from 8 centers of Russia, Ukraine and Kyrgyzstan were received and analyzed. An original questionnaire was developed for this study on the basis of the current clinical guidelines. Conclusion: The final results of a prospective survey revealed an insufficient level of students' basic knowledge of diagnosis, treatment and prevention of CAP. The study revealed a statistically significant heterogeneity of knowledge levels in different centers, which indicates the need for the introduction of unified and in-depth training programs in this area.